Petrographic investigation on recycled coarse aggregate and identification the reason behind the inferior performance - Mistri, Abhijit; Bhattacharyya, S.K.; Dhami, Navdeep; Mukherjee, Abhijit; Barai, S.V. (ELSEVIER SCI LTD, 2019)
Recycled concrete aggregate (RCA) shows more complex behavior in fresh and hardened concrete due to its higher water absorption, weak bonding capacity, poor interfacial transition zones (ITZs) and other uncertainties. The old attached mortar (AM) of RCA is the primary reason behind this. Petrographic analysis is normally assessed for construction aggregate to evaluate the physical and mineralogical characteristics, along with these the prediction of aggregate behavior in concrete. The same methodology is applied here for RCA and demanding to investigate the reason behind the inferior performance of it into fresh concrete. Optical microscopy, thin section, and Scanning Electron Microscopy (SEM) analysis are carried out in order to solve the addressed issue. Both the qualitative and quantitative petrographic analysis is conducted in order to identify the inferior properties of RCA. Micropores and microcracks are very common for RCA surface which propagates the failure of recycled aggregate concrete (RAC) under load. The experimental observation is suggested that the RCA is different kind of aggregate for sustainable construction material and cannot comparable with natural aggregate (NA) without proper understanding the type of parent aggregate or source of RCA. The range of aggregates between 20 and 10 mm can give good quality RCA after additional crushing and suitable treatment is required on RCA for strengthening the old ITZ and AM in order to achieve high-quality RCA.